Keefektifan Penggunaan Media Lagu dalam Pembelajaran Menulis Puisi Siswa Kelas VIII I SMPN 1 Jember - Rohmah Juwita Sari; Anjar Putro Utomo (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
The purposes of this study were to describe the effectiveness of using song media in poetry writing skill for VIII I SMP N 1 Jember students. The data of this study were from the result of poetry writing skill pre-test and post-test by using song media in VIII I SMP N 1 Jember. Based on the result of data analysis and discussion, it can be concluded that (1) poetry writing skill of VIII I SMP N 1 Jember students without using song media with average 58,33, and (2) poetry writing skill VIII I SMP N 1 Jember students by using song media with average 72,26.